FUTURE TASKS OF MEASURES TO REDUCE POVERTY IN SOCIETY BASED ON THE PRINCIPLE OF HUMAN VALUE (Scientific journal of the Fergana State University, 2023)
In this article, the future tasks of measures to reduce poverty in the society based on the principle of human dignity in New Uzbekistan are revealed based on specific examples, and the social philosophical analysis of ensuring the peaceful and safe life of the citizen of our country, his fundamental rights and freedoms is highlighted. The article also presents the programmatic foundations of the fight against poverty.